Slay - Morris, Brittney (New York : Simon Pulse, 2019)
An honors student at Jefferson Academy, seventeen-year-old Keira enjoys developing and playing Slay, a secret, multiplayer online role-playing game celebrating black culture, until the two worlds collide.
Junior Library Guild
Ages 15-17.
Grades 10-12.
930
A Junior Library Guild selection
Keywords: African Americans -- Juvenile fiction; Dating (Social customs) -- Juvenile fiction; Fantasy games -- Juvenile fiction; High schools -- Juvenile fiction; Role playing -- Juvenile fiction; Video games -- Juvenile fiction; African Americans -- Fiction; Dating (Social customs) -- Fiction; Fantasy games -- Fiction; High schools -- Fiction; Role playing -- Fiction; Schools -- Fiction; Video games -- Fiction; African Americans -- Fiction; Dating (Social customs) -- Fiction; Fantasy games -- Fiction; Role playing -- Fiction; School stories; Video games -- Fiction